Grabbike User Loyalty In Medan: Is Brand Engagement And Quality Perception Decisive? - Gilbert Powell Eklesia Manik; Muhammad Dharma Tua Putra Nasution (UNIVED Press, 2026)
This study aims to examine the influence of brand engagement and perceived quality on customer loyalty in the context of GrabBike, a digital ride-hailing service in Medan, Indonesia. The research focuses on understanding the extent to which emotional and functional dimensions drive customer loyalty within digital service ecosystems. The study adopts an explanatory quantitative approach using a structured survey. Primary data were collected from 78 active GrabBike users in Medan. The data were analyzed using multiple linear regression via SPSS version 26, preceded by validity, reliability, and classical assumption tests. The results indicate that brand engagement significantly influences customer loyalty (β = 1.015; p < 0.01), whereas perceived quality does not show a significant partial effect (β = 0.032; p = 0.881). However, both variables jointly have a significant effect, as reflected by an F-value of 24.992 (p < 0.001) and an Adjusted R² of 0.384. The findings suggest that customer loyalty in digital services is shaped more by emotional engagement than by perceptions of service quality alone. Therefore, service providers like GrabBike should enhance brand engagement through personalized, participatory communication strategies and long-term user interaction. This study contributes to the literature on customer loyalty in digital services by highlighting the limited direct role of perceived quality and reinforcing brand engagement as a key determinant. It also adds value by exploring a geographically underrepresented urban setting—Medan—as a case study outside Java Island.